Pengaruh Shopping Lifestyle, Discount, Fashion Involvement, Hedonic Shopping Motivation, Dan Promosi Penjualan Terhadap Impulse Buying (Studi Kasus Pada Mahasiswi Yang Pernah Berkunjung Ke Center Point Di Mall Olympic Garden Malang) - Devyasari Octavia Irawan; Rois Arifin; Muhammad Ridwan Basalama (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT This study aims to determine and analyze shopping lifestyle, discounts, fashion involvement, hedonic shopping motivation, and sales promotion of impulse buying among female students who have visited the Center Point at Mall Olympic Gardem Malang, both partially and simultaneously. This research uses explanative research with a quantitative approach. The population in this study were female students who had visited Center Point at the Olympic Garden Mall in Malang. Samples taken as many as 110 respondents. The sampling technique used is accidental sampling. Data were analyzed using multiple linear regression analysis processed with SPSS16.0 software. The data collection method used was a questionnaire. The results showed that Shopping Lifestyle, Discount, Fashion Involvement, Hedonic Shopping Motivation, and Sales Promotion simultaneously affected Impulse Buying. While Discount and fashion involvement have a partially significant effect on Impulse Buying. And, Shopping Lifestyle, Hedonic Shopping Motivation, and Sales Promotion have no significant effect partially on Impulse Buying.Keywords: Shopping Lifestyle, Discounts, Fashion Involvement, Hedonic Shopping Motivation, Sales Promotion, and Impulse Buying.